From Organization to Enterprise: The Institutional Factors Shaping Student Entrepreneurial Engagement in Higher Education - Bajarias, Anne Jere; Pacubas, Christina; Payod, Elisa; Gabuya, Florenda; Yamagishi, Kafferine; Ybañez, Adrian P. (Journal of Cultural Analysis and Social Change, 2025)
Entrepreneurial engagement among students is increasingly recognized as a vital component of higher education’s contribution to economic development, yet limited empirical research explores how organizational climates within student organizations foster such engagement, particularly in developing countries. This study examines the institutional and organizational factors associated with student entrepreneurial engagement in Philippine higher education institutions, focusing on organizational commitment, entrepreneurial leadership, organizational support, access to finance, location advantages, and innovative culture. Using a quantitative, cross-sectional design, data were collected from 916 student organization members and analyzed through descriptive statistics, reliability analysis, and Pearson correlation. Findings indicate high levels of perceived organizational support, innovative culture, organizational commitment, and entrepreneurial engagement, suggesting that student organizations operate within environments that encourage initiative, collaboration, and creativity. Correlation results reveal significant positive associations among all variables, with innovative culture (r = .693), organizational support (r = .676), and entrepreneurial leadership (r = .618) emerging as the strongest correlates of entrepreneurial engagement. These associations underscore the ecosystemic nature of student entrepreneurship, wherein structural support, leadership practices, and innovation-oriented cultures collectively shape student involvement in entrepreneurial activities. Access to finance showed only moderate perceptions yet remained significantly associated with entrepreneurial engagement, highlighting persistent resource constraints. The study contributes to entrepreneurship education literature by positioning student organizations as critical sites of entrepreneurial learning and by emphasizing institutionally embedded, association-based mechanisms rather than causal or predictive pathways. Implications for policy and practice include the need to strengthen support systems, expand financial access, enhance leadership capacity, and cultivate innovation-driven organizational cultures to promote student entrepreneurship.